The Effects of Knowledge Extraction Approaches on Cryptanalysis Studies and Analysis of the Success of Chaos-Based Countermeasures - Bürhan, Yücel; Özkaynak, Fatih (Springer Science and Business Media Deutschland GmbH, 2023)
Each new approach and scientific progress provides many advantages and innovations from theory to practice yet, its disadvantages should be evaluated comprehensively from different perspectives. In this study, the effects of knowledge extraction approaches on the cryptanalysis process have been evaluated. It is known that the secret key of the encryption algorithm can be obtained by using knowledge extraction approaches, especially with application oriented attacks such as side channel analysis. It is known that chaotic masks can be used as a countermeasure to prevent the success of these attacks. In this study, side-channel analyzes of the chaos-based substitution box structures that have been proposed in recent years have been carried out. The side channel analysis results of the existing studies in the literature have been carried out for the first time in this study. The results obtained showed that the approaches in the field of knowledge extraction should be handled more comprehensively in the cryptanalysis processes, and also pointed out that a new evaluation criterion should be analyzed for future studies for chaos-based design studies. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Chaotic mask; Cryptanalysis; Knowledge extraction; Substitution box